AKTIVITAS KEMAMPUAN MEMORI SPASIAL FRAKSI ETIL ASETAT HERBA MENIRAN MERAH (PHYLLANTHUS URINARIA L.) DENGAN METODE RADIAL ARM MAZE - Karunita Ika Astuti (BORNEO JOURNAL OF PHARMASCIENTECH, 2019)
ABSTRACTIntelligence is an ability to adjust with the environment by blends of attention, concentrationand short term memory. Phyllanthus urinary L. is a plant that have active content offlavonoid compound especially quersetin which efficacious in spatial memory activity. Thepurpose of this study was to determine, effective dose and histopathology of gyrus dentatus inanimal test after given ethyl acetate fraction of meniran herb. The research was conducted by administration of ethyl acetate fraction with doses 50 mg/kgBW, 100 mg/kgBW and 150mg/kgBW for 10 days to white male mice. The research to view error in memory by radialarm maze (RAM). Positive control using quercetin 42 mg/kg BW and negative control usingNa-CMC 0.5%. The most effective result at dose 100 mg/kgBW with shows value of 38.619%± 2.56, the best and smaller value if compared with 50 mg/kgBW and 100 mg/KgBW andnegative control, 49.195%±4.27; 53.130%±1.70; and 63.419%±4.55, respectively withpositive control value of 32.424%±9.13.Keywords: Radial arm maze, ethyl acetate fraction, red meniran (Phyllanthus urinary L.)